The effect of soil amendment and the soil microflora on the survival of Helminthsporium sativum, the crown rot pathogen of wheat, in a virgin soil from the western Transvaal - Jooste, W. J (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1970.